2022
DOI: 10.1532/hsf.4443
|View full text |Cite
|
Sign up to set email alerts
|

The Simple Technique of Sternal Closure Using An Absorbable Mesh Plate

Abstract: Background: Several authors have investigated various sternal closure materials and technologies for sternal fixation; nonetheless, the optimal technique for primary sternal closure remains unclear. This study aimed to evaluate the sternal stability of a simple technique using a mesh-type plate (Super Fixorb MX40®; Takiron Co. Ltd., Osaka, Japan), as compared with wire cerclage. Methods: A total of 70 patients who underwent cardiovascular surgery through median sternotomy between July 2019 and May 2020 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…1, we devised this method assuming that sandwiching the sternum between the plates would prevent sternal displacement and postoperative bleeding by tightly aligning the sternal bone marrow. Axial CT evaluation on postoperative day 5 showed a signi cantly less sternal step-off and less postoperative substernal hematoma formation in group M than in group P (Table 4), which was similar to the study by Watanuki et al who reported less anteroposterior sternal displacement [14]. In our multivariate analysis of postoperative CT data for substernal hematoma, the mesh plate was an independent predictor of substernal hematoma prevention.…”
Section: Discussionsupporting
confidence: 89%
“…1, we devised this method assuming that sandwiching the sternum between the plates would prevent sternal displacement and postoperative bleeding by tightly aligning the sternal bone marrow. Axial CT evaluation on postoperative day 5 showed a signi cantly less sternal step-off and less postoperative substernal hematoma formation in group M than in group P (Table 4), which was similar to the study by Watanuki et al who reported less anteroposterior sternal displacement [14]. In our multivariate analysis of postoperative CT data for substernal hematoma, the mesh plate was an independent predictor of substernal hematoma prevention.…”
Section: Discussionsupporting
confidence: 89%
“…1 , we devised this method assuming that sandwiching the sternum between the plates would prevent sternal displacement and postoperative bleeding by tightly aligning the sternal bone marrow. Axial CT evaluation on postoperative day 5 showed a significantly less sternal step-off and less postoperative substernal hematoma formation in group M than in group P (Table 4 ), which was similar to the study by Watanuki et al who reported less anteroposterior sternal displacement [ 13 ]. In our multivariate analysis of postoperative CT data for substernal hematoma, the mesh plate was an independent predictor of substernal hematoma prevention.…”
Section: Discussionsupporting
confidence: 88%